Academic Staff’s Apathy towards Formal Professional Development Programmes at North-West University - Pelser, Theuns G.; Makunye, Matthews M (South African Journal of Higher Education, 2016)
The purpose of this study was to explore reasons for academics’ apathy towards formal professional development programmes at North-West University. The research design was essentially descriptive, employing both qualitative and quantitative research techniques to gather and analyse data. Three techniques, namely, questionnaire surveys, analysis of university documentary sources on professional development, and literature review, were utilised to obtain information. Despite all the perceived impediments to professional development, the respondents felt optimistic that with the necessary interventions, the outlook of professional development in Higher Education Institutions (HEI) is positive. However, there is an urgent need to take stock of the effectiveness of the current professional development initiatives and the findings from this study would serve as a basis for professional development initiatives in HEI. To this end the University needs to institute periodic needs assessment for professional development for both academics and the Institutions as a whole.